Aberrant Diffuse Intense CD10 Expression In P16 Positive Undifferentiated Endometrial Carcinoma: A Diagnostic Dilemma. (28th October 2020) - Derakhshandeh, R; Kallakury, B
Abstract: Introduction/Objective: High-grade endometrial neoplasms frequently pose a diagnostic challenge on purely histologic evaluation due to their ambiguous morphologic features. High grade endometrioid adenocarcinoma, serous carcinoma, undifferentiated carcinoma, and a minority of sarcoma cases can present with a solid growth pattern. Methods: We present a 59-year-old patient who underwent a hysterectomy and bilateral salpingo-oophorectomy for a biopsy proven FIGO grade 2 endometrial carcinoma. Results: Grossly, the entire endometrial cavity was involved by a hemorrhagic tumor. Microscopic examination showed the entire specimen to be replaced by predominantly non-cohesive diffuse sheets of mitotically active, pleomorphic cells without any glandular, papillary, serous or clear cell features.The differential diagnosis included undifferentiated carcinoma, serous carcinoma, carcinosarcoma, stromal sarcoma and other tumors including high- grade lymphoma. By immunohistochemistry, the tumor cells showed variable positivity for CK7, EMA, CK19, CK18, CK8, AE1/AE3, pan-keratin, CAM5.2, CD56, synaptophysin, p53, cyclinD1 and with a high Ki-67 proliferation index of 80%. The tumor was diffusely/intensely positive for CD10 and P16 while being negative for ER, PR, PAX8, HPV, mesenchymal and lymphoid markers. While diffuse/intense CD10 positivity and ER/PR negativity raised a concern for stromal sarcoma component, the above phenotype confirmed an aggressive/high grade carcinoma. Diffuse/intense p53 and p16 expression raised a consideration of serous carcinoma, but morphology and absence of PAX-8 failed to support this diagnosis. Undifferentiated carcinoma of the endometrium is a high-grade carcinoma which has been recognized as a distinct entity with diffuse p16 and p53 positivity in the absence of PAX-8 and hormone receptors. Positive vimentin, along with a negative HPV, confirmed the endometrial rather than cervical origin of this neoplasm. Conclusion: By reporting this case, we draw attention to the previously unreported diffuse intense CD10 expression in undifferentiated carcinoma of endometrium to avoid misdiagnosis with considerations that include stromal sarcoma.